2019
DOI: 10.1016/j.hpb.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of postpancreatectomy hemorrhage: a systematic review and meta-analysis

Abstract: Background: Postpancreatectomy hemorrhage is a potentially lethal complication after pancreatic resection. The objective of this systematic review is to provide insight in the current status of incidence, detection, management and clinical outcomes of late postpancreatectomy hemorrhage. Methods: A systematic search was conducted on the literature from February 2007 to July 2018 in PubMed, Embase and the Cochrane library. Included were clinical studies with clinical outcomes on late postpancreatectomy hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
60
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 26 publications
9
60
0
15
Order By: Relevance
“…In our study, all four patients who underwent superselective embolization for a GDA pseudoaneurysm had recurrent hemorrhage. By contrast, in the hepatic artery sacrifice group, 2 (18%) of the 11 patients had recurrent hemorrhage, indicating a lower incidence rate and a rebleeding rate comparable to that in other studies (Biondetti et al 2019;Floortje van Oosten et al 2019). Therefore, our results support the finding that the destructive approach is more effective than superselective embolization in managing delayed PPH.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, all four patients who underwent superselective embolization for a GDA pseudoaneurysm had recurrent hemorrhage. By contrast, in the hepatic artery sacrifice group, 2 (18%) of the 11 patients had recurrent hemorrhage, indicating a lower incidence rate and a rebleeding rate comparable to that in other studies (Biondetti et al 2019;Floortje van Oosten et al 2019). Therefore, our results support the finding that the destructive approach is more effective than superselective embolization in managing delayed PPH.…”
Section: Discussionsupporting
confidence: 86%
“…Rare postoperative hemorrhage after robotic-assisted pancreatoduodenectomy for pancreatic head cancer: a case report approximately 2-10% develop post-pancreatectomy hemorrhage (PPH), a life-threatening complication with the reported mortality rate of 20-50% (8,9). Here, we report a male patient who experienced PPH with a very rare cause after RAPD.…”
Section: Case Reportmentioning
confidence: 89%
“…Nonetheless, the occurrence rate of postoperative complications is high. PPH is the most common and dreaded complication after PD and is associated with mortality rates of as high as 21% (9). A recent study reported that 3.8% of 105 patients who underwent robotic PD experienced PPH (10).…”
Section: Discussionmentioning
confidence: 99%
“…1). [34,[41][42][43][44] In the "draining-tract-targeted" management of POPFs, treatment was started as soon as possible after diagnosing a POPF to reduce the risk of subsequent life-threatening complications (Fig. 1) [34].…”
Section: Discussionmentioning
confidence: 99%